Emotional Responses to a Sexual Assault Threat: A Qualitative Analysis Among Women With Histories of Sexual Victimization - Silver, Kristin E. (Journal of interpersonal violence, 2022)
Sexual assaults against women are a leading threat to human rights and public health in the United States. Considering the high rates of sexual revictimization among women and the limited understanding of the mechanisms which fuel this phenomenon, the goal of the present study was to investigate the role of emotion in coping with a hypothetical threat of sexual assault for previously sexually victimized college women. A total of 114 college women with a history of sexual victimization listened to an audio-recording describing a sexual assault scenario and then described how they felt. A qualitative analysis paradigm was used to capture participants’ responses in an open-ended, real-time, experiential manner. Data were analyzed using Consensual Qualitative Research—Modified methodology. Four main themes emerged (Negative Reactions, Indifferent Evaluations, Active Responses, and Cognitive Appraisal of the Situation), along with various subcategories, demonstrating the variability of women’s responses to a sexual assault threat. Many women experienced uncomfortable or distressing emotional reactions to the vignette, primarily through discomfort, but also through anger, anxiety, and being upset. Few women reported experiencing fear, and a small number reported experiencing self-blame. The low endorsement of fear and anger in our high-risk sample indicates emotional dysregulation as a potential mechanism of repeated sexual victimization and a promising target for clinical intervention. Overall, results may inform sexual assault risk reduction efforts and the empowerment of women who have experienced sexual victimization.